Mistakes were made ebook - Pastis, Stephan (Timmy Failure, 2013)
Want to aspire to greatness? Check out this new edition of Timmy Failure's first adventure. He may be clueless, but the comically self-confident Timmy Failure is CEO of the best detective agency in town, perhaps even the nation.